Athenian generals : military authority in the classical period - Hamel, Debra. (Mnemosyne, Supplements, 1998)
This study of the Athenian strategia is concerned with identifying the locus of military authority in the Athenian polis . Consideration of the role played by generals in the deliberative and final stages of military expeditions and of the relationship between strategoi and their subordinates, colleagues, and the Athenian demos itself suggests that Athens' generals did not exercise significant authority over their city's military operations. Rather, the demos controlled its generals both by means of its direct involvement in decision-making related to campaigns and by establishing in Athens a climate of fear which was very often sufficient to dissuade generals from acting in opposition to the Athenians' will. This volume is important reading for anyone who is interested in ancient military history or the question of sovereignty in Athens.